Faktor-Faktor Yang Mempengaruhi Ibu Dalam Pemberian Asi Ekslusif Di Desa Candi Rejo Kecamatan Sibiru-Biru Tahun 2013 - Singarimbun, Nurbaiti Br (Institute Of Computer Science (IOCS), 2019)
Breast milk is the best food for infanst 6 months of age. ASI can meet the nutritional needs of infanst up to the age of 6 month without any food addives. This is called excelusive breastfeeding. In reality, not all mothers breast their babies exclusively. This study aims to determine the factors that influence exclusive breastfeeding mother in Village of  Candi Rejo District of Sibiru-biru in 2013. This type of research is survey. The study population where all mothers with infants 6-12 months of age who reside in the Village of Candi Rejo District of Sibiru-biru totaling 110 people and serve as the overall sample. The factors of affecting exclusive breastfeeding is used by multiple logistic regression. The result  showed that the factors-factors that affect mothers in exclusive breastfeeding is the mothers of knowledge (p=0.000), maternal attitude (p=0.000), mother’s occupation (p=0.002), number of children mothers (p=0.000), support husband (p=0.000), promotion of infant formula (p=0.000). The most dominant variables associated with exclusive breasfeeding is the promotion of infant formula variable (p value = 0.000 ; OR=14.026). It is recommended to mothers who have infants aged 6-12 months in on order to actively search for information by following the extension activities so that increasing maternal knowledge as well as having a positive reaction to do so, and the mother’s knowledge , than it is likely not to believe in the promotion of infant formula. To the mother in order to follow the extension of the health center, associated with exclusive breastfeeding. Husbands also to be able to provide emotional support, attention to nutritional intake for the wife. To health workers, counselors to be able to add energy to improve Communication, Information, Education and Communication (IEC). To the company, and work places are suggested to provide facility space for breasfeeding.